Efficacy of Homeopathic Complexes in Gastrointestinal Nematode Control in Sheep - de Souza, Ubiratã Mariano; da Costa, Ricardo Lopes Dias; Katiki, Luciana Morita; Giglioti, Rodrigo; Zadra, Lenira El Faro; Rodrigues, Leandro; Veríssimo, Cecília José (Homeopathy, 2025)
Gastrointestinal worm infestation, mainly by H. contortus, represents one of the main health challenges in sheep farming, exacerbated by resistance to conventional anthelmintics. This study evaluated the efficacy of two homeopathic complex formulations in reducing parasite load in ewes (not lactating/not pregnant) over a period of 45 days.Thirty Santa Inês and Dorper crossbred sheep were used, distributed in three treatments: T1 (Apis mellifica 15cH + Arsenicum album 11cH + Cina 9cH + Kalium phosphoricum 15cH + Spigelia anthelmia 9cH + Pereskia aculeata 6cH), T2 (the constituents of T1 but replacing Pereskia aculeata by Ferrum metallicum 6cH) and T3 (control group, without homeopathic treatment). The animals were evaluated by counting the EPG (eggs per gram of feces), monitoring level of anemia by the grade of ocular mucosal coloration (FAMACHA® method) and measuring body weight on each of days 0, 15, 30 and 45.The results showed a significant (p < 0.05) decline in EPG from the 30th day, being more pronounced in group T2, which showed 79% efficacy on the 45th day. There were no significant differences between the treatments related to FAMACHA® score or daily weight gain.The homeopathic complexes used in this study, particularly T2 which contains Ferrum metallicum 6cH, contributed to the control of gastrointestinal nematode infection in dry ewes.
Keywords: gastrointestinal nematodes; Haemonchus contortus; homeopathy; sheep